Digital Marketing Application to Increases Livestock Sales in Sacrificial Cages in Ganggang Panjang Sidoarjo Village Based on Android: Aplikasi Digital Marketing Meningkatkan Penjualan Ternak pada Kandang Qurban di Desa Ganggang Panjang Sidoarjo Berbasis Android - Refinda, Achmad Ainun Gusti; Fitrani, Arif Senja (Procedia of Engineering and Life Science, 2023)
The need for qurban animals both for the needs of the Eid al-Adha holiday and needs other than Eid al- Adha such as aqiqah, or other important events are very much needed where in the selection of sacrificial animals such as goats or cows are both very important. types of sacrificial goats and cows, the condition of the sacrificial animals so that the results given are very good. In the process of selecting, purchasing, distributing sacrificial animals, they still use the manual method, which is less efficient, so there is a need for an application system that can assist in selecting, purchasing, and distributing sacrificial animals. In running the business, most of the service processes that are applied are still manual by checking the condition of the animal by coming to the place so that it is difficult for the customer to come twice or contact by phone. Then, in managing transaction data and issuing notes, it is also still manual. "DIGITAL MARKETING APPLICATION TO INCREASING LIVESTOCK SALES IN QURBAN STAGES IN GANGGANG PANJANG VILLAGE, SIDOARJO BASED ON ANDROID" was created to simplify the process of buying and selling livestock services so as to facilitate work and improve service in these small and medium enterprises. From the results of this study it can be concluded that this system can increase effectiveness because it is not done manually, the features in the information system are easy to use and the transaction data management runs well.